Vitamin D and breast cancer: evidence for biological and clinical significance. (July 2012) - Clark, Amy S; DeMichele, Angela
SUMMARY Both vitamin D deficiency and breast cancer are common. Laboratory evidence strongly suggests a biological role for vitamin D in normal breast cellular maintenance. Clinically, however, definitive associations between vitamin D and breast cancer risk and outcome have been challenging to decipher. A myriad of epidemiological studies have attempted to connect vitamin D with breast cancer risk, stage at diagnosis and outcome, but results vary. Here, we will closely examine the biologic evidence that supports an association between vitamin D and breast cancer and summarize the epidemiologic and clinical studies in this area. We will discuss ongoing trials and additional research questions that should be addressed in future studies.